A Study of the inhibitory effect of Terpinen-4-ol on Amastigote Forms of Leishmania tropica within Macrophages of Mouse in vitro - Abdulazim Mohammed Hami (Iraqi Journal of Pharmaceutical Sciences, 2022)
It was recorded that Terpinen-4-ol has an anti-parasitic properties, so it will be noteworthy to intensify the studies about this compound.